(untitled) (Research, Society and Development, 2020)
Introduction: Prostitution has always been an activity related to taboos and stigmas, including in health services, where they usually focus only on reproductive and sexual clipping in women who perform this activity. Objective: To analyze the level of symptoms of Common Mental Disorders, quality of life and their correlations among female sex workers. Method: A cross-sectional, exploratory, quantitative study was conducted with 158 women, using the WHOQOL-Bref e and the Self Report Questionnaire (SQR-20), with p <0.05. Results: The physical domain had the best performance with 66.48; and the domain of social relations was the worst score with 55.30. More than half of participants (51.6%) have signs and symptoms indicative for Common Mental Disorders (CMD). All quality of life domains are closely related to the absence or presence of CMD. Conclusion: It is necessary and urgent to broaden the mental health focus of health professionals to the person in prostitution.